Second homes Tourism in the south coast of Brazil: a discussion about its dimension and relevance for contemporary tourism activity - Abrahão, Cinthia Sena (2018)
The objective of this article is to analyze the dimension of the second coastal tourist home in the southern region of Brazil, considering the premise that this phenomenon persists relevant in the scope of tourism activity, both internationally and nationally. The second home is understood as a non-hotel type of tourist accommodation, in which there is a permanent bond, but whose permanence does not exceed the period of one year. Particular aspect refers to its connection with the civil construction activities as well as the real estate market. The relative invisibility of the phenomenon of second residence in the databases that subsidize the elaboration of public policies and actions related to tourism, both at the national level and in the states, is problematic. In terms of methodology, the approach of the theme in this clipping was quantitative and exploratory in nature. The exploratory perspective guided the literature review, with a view to understanding the public policy of tourism development and its priorities, as well as discussing the phenomenon of the second tourist residence and the way in which it has been approached. The analysis of the secondary data involved collection, systematization and interpretation, in order to make explicit the participation and the growth of the volume of second residences of the coast. Data were collected exclusively for the coastal municipalities of the three southern Brazilian states at the IBGE bases. Then, comparative data were analyzed regarding the tourism map, in which the tourist destinations are classified. The results reiterate that the disregard of these flows and territorial dynamics in the context of tourism public policy tends to generate strong distortions in the planning, implementation and results that can be obtained. It is understood that their apprehension, however, requires an effort of surveying, systematization and statistical analysis different from that which must be undertaken to measure the economic flows coming from the business establishments related to lodging.